2008
DOI: 10.1037/0096-3445.137.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Spatial localization of touch in the first year of life: Early influence of a visual spatial code and the development of remapping across changes in limb position.

Abstract: Two experiments investigated infants' ability to localize tactile sensations in peripersonal space. Infants aged 10 months (Experiment 1) and 6.5 months (Experiment 2) were presented with vibrotactile stimuli unpredictably to either hand while they adopted either a crossed-or uncrossed-hands posture. At 6.5 months, infants' responses were predominantly manual, whereas at 10 months, visual orienting behavior was more evident. Analyses of the direction of the responses indicated that (a) both age groups were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
131
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 88 publications
(128 reference statements)
9
131
0
Order By: Relevance
“…Bremner et al (2008) find that this is not present at 6 months but develops by 10 months of age. There are a range of differences between the procedure used by Bremner et al (2008), and that used in the current study which might explain the different ages at whcih infants demonstrated competence.…”
Section: Visual-tactile Co-location In Infants 12mentioning
confidence: 67%
See 4 more Smart Citations
“…Bremner et al (2008) find that this is not present at 6 months but develops by 10 months of age. There are a range of differences between the procedure used by Bremner et al (2008), and that used in the current study which might explain the different ages at whcih infants demonstrated competence.…”
Section: Visual-tactile Co-location In Infants 12mentioning
confidence: 67%
“…Indeed, as a result of eye movements, these computational challenges also impinge on our ability to detect co-location between visual and auditory stimuli (Pöppel, 1973). Research with infants indicates that an ability to incorporate information about posture into sensory processing develops gradually across the first year of life (e.g., Bremner et al, 2008; …”
Section: Visual-tactile Co-location In Infantsmentioning
confidence: 99%
See 3 more Smart Citations